Keputusan Pembelian Produk UMKM Tasikmalaya: Analisis Peran Label Halal, Ijin BPOM dan Kepercayaan - Dermawan, Muhammad Jagat (Mutawasith: Jurnal Hukum Islam, 2024)
This study aims to investigate the factors that influence the purchasing decisions of MSME products (Micro, Small, and Medium Enterprises) in Tasikmalaya with a focus on the role of halal labels, BPOM permits and consumer trust. The method used is a quantitative method with a path analysis model. The research sample was selected using the Simple Random Sampling method by considering relevant consumer characteristics. To identify the relationship between the variables studied and their impact on purchasing decisions of MSME products in Tasikmalaya, data collected from respondents were then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique. The results of this study indicate that halal labels and BPOM permits have a significant influence on consumer trust and purchasing decisions of MSME products in Tasikmalaya. In addition, consumer trust is proven to act as an intervening variable, strengthening the relationship between halal labels and purchasing decisions.